PELAKSANAAN KEBIJAKAN REHABILITASI SOSIAL BAGI DISABILITAS MENTAL OLEH UNIT PELAKSANA TEKNIS BINA LARAS DINAS SOSIAL PROVINSI RIAU TAHUN 2018 - Fadillah, Ressi Nur; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Social rehabilitation is a process of recovery and development of social services activities in a whole and integrated manner so that persons with mental disabilities (ex psychotic) can carry out their social functions properly in social life. Social rehabilitation is one of the rights of persons with mental disabilities in the welfare of their lives which has physical, intellectual, mental, and sensory limitations. Social rehabilitation in the Technical Implementation Unit (UPT) Bina laras of the Riau Province Social Service seen from Edward III's Public Policy Implementation Theory, namely, Communication, Resources, Disposition, and Bureaucratic Structure. Based on this theory, it is found that there are obstacles in the implementation of social rehabilitation policies for mental disabilities in the UPT Bina Laras Social Service of Riau Province.The purpose of this study was (1) to describe the Implementation of Social Rehabilitation Policy for Mental Disabilities by UPT Bina Laras Social Service, Riau Province in 2018. (2) to describe the factors that hinder the implementation of Social Rehabilitation Policy for Mental Disability by UPT Bina Laras Social Service Riau Province 2018.The implementation of the Social Rehabilitation Policy at the UPT for the Development of the Social Services Office in Riau Province is carried out through 7 (seven) stages, namely: a. Initial Approach, b. Assessment, c. Preparation of Intervention Plans, d. Implementation of Interventions, e. Resocialization, f. Evaluation / Further Guidance, and g. Termination. Then, from the 7 (seven) stages there are 2 (two) stages that have not been maximized, namely Intervention Implementation stage and Resocialization stage. There are 4 (four) factors that hamper the implementation of social rehabilitation policies for mental disabilities especially in the 2 (two) stages, namely, the lack of professional experts in implementing social rehabilitation policies for mental disabilities, limited budget in implementing social rehabilitation policies for mental disabilities, lack of facilities and infrastructure (facilities) in the implementation of social rehabilitation policies for mental disabilities, and the implementation of social rehabilitation policies for mental disabilities that are not in accordance with the SOP (Standard Operating Procedures) as determined by the UPT Bina Laras Social Service of Riau Province. Keywords: Implementation, Policy, Communication, Resources, Disposition, Bureaucratic Structure, Social Rehabilitation, Mental Disability